Arm's Length Relationships - Cremer, J. (Quarterly Journal of Economics, 1995)
We show that lowering the cost of acquisition of information that a principal obtains about the performance of an agent may make it more difficult for the principal to commit to threats. Hence it will weaken incentives and can therefore be counterproductive. This phenomenon is explored in a framework where improving the quality of information makes a commitment not to renegotiate less credible. Applications to the theory of the firm are briefly explored.